Response of Foxtail Millet (Setaria italica) to Nitrogen and Phosphorus under Rainfed Conditions of Northern Dry Zone of Karnataka - Kalaghatagi, S B; Jirali, D I; Wali, S Y; Nagod, M S (Annals of Arid Zone, 2016)
A field experiment was conducted for two consecutive rainy seasons of 1991 and 1992 at Regional Research Station. Bijapur (Karnataka), to study the response of foxtail millet to various levels of nitrogen and phosphorus under rainfed conditions. Grain and fodder yields of foxtail millet were significantly higher (516 and 1485 kg ha.', respectively) with the application of 45 kg N ha.' compared to 0, 15 and 30 kg N ha.'. In pooled data, application of 45 kgN ha.' increased the grain yield by 184, 63 and 23% compared to 0. 15 and 30 kg N ha.', respectively. There was no response to phosphorus application. The interaction effects were non-significant